Niccolò Machiavelli: klasyczny realizm i republikanizm - Raburski, Tomasz (Wydawnictwo Naukowe Instytutu Filozofii, 2012)
Article presents life and ideas of Niccolò Machiavelli. Machiavelli is placed in the context of his times. His influence on the development of modern political thought is examined. The examples of his wider impact on western culture are given. Machiavelli is described as a founding father of two strands of political philosophy: political realism and republicanism.
Niccolò Machiavelli: political realism and republicanism
Keywords: Machiavelli; political realism; republicanism; Italian philosophy; early modern philosophy; renaissance philosophy